Analisis Efektivitas Penggunaan QR Kode sebagai Sarana Pembayaran Digital terhadap Minat Beli Konsumen di MP Mart - Ilham Pangestu, Mahardika; Cahyani, Leni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effectiveness of using QR codes as a means of digital payment on consumer buying interest at MP Mart. The research method used is Descriptive Qualitative. The data to be collected using a sample of 3 people who influence buying interest in MP mart. Data analysis techniques with the AIDA model (Awareness, Interest, Desire, and Action). The results showed that in terms of awareness the use of QR codes has a significant positive impact on consumer buying interest in MP Mart. Then, in terms of Interest QR Code makes payment transactions easier. In terms of Desire, consumers and sellers are very satisfied with the facilities provided by the QR Code. Finally Action, the execution of using the QR Code needs to be socialized more widely. With the results of this research, according to the AIDA Model, the use of QR codes as a means of digital payment at MP Mart is declared Effective.